An Industrial systems design study on RBA Engineering Company - Aquino, Ryan Jose.; Deomano, Johanna Jeraldine; Go, Michelle Christine; Santos, Jose Angel (Diliman, Quezon City College of Engineering, 2001)
RBA Engineering is a car parts manufacturer located in Cainta, Rizal. The Company started its operation in 1984 with Mitsubishi Motors Philippines Corporation (MMPC) as its only customer. The Company specializes in the manufacture of steel car parts for MMPC products such as the Adventure, Strada, Pajero, Canter and L300 vans. This industrial systems design study aims to analyze the current supply chain management setting and techniques RBA Engineering Company is presently employing. This study also aims to provide the company with other supply chain management strategies which may assist the company in its planned expansion and competitiveness. This study is divided into 3 major parts: company documentation, problem identification and recommendations. The first major part completely documented the supply chain activities of the company in the following areas: Purchasing, Inventory Management, Raw Materials Warehousing, Manufacturing, Finished Goods Warehousing, Transport Operations and Customer Service Operations. The second major part of the study dealt with the identification of the Supply Chain Management problems the company is currently experiencing. Using the streamline analysis chart, the following problems were identified. 1) Lack of formal means to ensure quality, 2)No Set time for accepting deliveries, 3)Inappropriate storage containers, 4)Lack of feedback mechanism, and 5)Disorganized warehousing of finished goods. The third part of the study dealt with the recommendation on each problem. Alternatives were generated and evaluated based on a devised set of criteria. After evaluation, the following alternatives were chosen: 1) Implementation of Vendor Quality Assurance Program, 2) Implementation of Delivery Window Strategy, 3) Implementation of a Revised Container System, 4) Implementation of a Customer Feedback Mechanism, and 5)Reorganization of Warehouse and Finished Goods Storage. The specifications of each program as well as the implementation schedule conclude the study in the Implementation Strategy section.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: RBA Engineering Company; Automobile industry and trade--Management.; Total quality management; System design